Application of Corn Starch and Red Galangal Coating to Extend the Shelf Life of Chrysanthemum Flowers (Chrysanthemum morifolium) - Darmawati, Emmy; Nabila Putri, Ivanka (PERTETA, 2024)
Chrysanthemum (Chrysanthemum morifolium) has high economic value. However, fresh Chrysanthemums are perishable and have a short shelf life. High respiration and microorganisms are the main causes of the decline in the quality of chrysanthemums after harvest. The fungus Puccinia horiana causes white rust disease on the leaves which were carried when the flowers are harvested and stored for distribution. Corn starch as an edible coating material combined with red galangal extract was expected to reduce damage by these two factors. The purpose of the research was to determine the best concentration of corn starch and red galangal extract to extend the shelf life of fresh chrysanthemum edible flower. The starch concentration chosen was based on the viscosity of the coating solution which can be applied by spraying and produces the solidness and smallest diameter of droplet. The concentration of 2% corn starch coating solution was chosen to be the best solution concentration for coating. In application, the coating solution used was 2% corn starch combined with 1% and 2% red galangal extract, with spraying done once and twice. The results of the study showed that the L2S2 formulation (2% galangal concentration with spraying 2 times) was the best treatment. This treatment can maintain flower water content at 86.02%, weight loss 19.00%, L value 34.50o, Hue value 347.04o on the 6th day of storage with a panelist assessment of a score of 3.25 (freshness, color, aroma). As a comparison, flowers without treatment (control) were still accepted by panelists up to the 3rd day of storage with a score of 3.01, more than 3 days the score was less than 3